THE UTILIZATION OF QUIZIZZ APPLICATION IN ONLINE ENGLISH LEARNING - Diah Widya Ningrum (STKIP Siliwangi, 2022)
One of learning applications that is commonly used in learning English is Quizizz. The purpose of this research was to determine the students’ perceptions of the effectiveness of using the Quizizz application in English courses. This research used a mixed method, namely quantitative method and qualitative method. The data collection method used was a questionnaire. Quantitative data collection was obtained with closed questions and qualitative data was collected with open questions. Based on the students’ perceptions, the Quizizz application is a learning application that is fun, effective, not boring, varied, challenging, simple, and can be used anywhere. However, the weakness of this Quizizz application is that it must have stable internet usage. There were also comments from students who hoped that more teachers would use the Quizizz application in the learning process on a regular basis. The conclusion of this research was that the utilization of the Quizizz application, in general, has a positive impact on the process of learning English.